Improving the technical efficiency of public health centers in Cambodia: a two-stage data envelopment analysis - Dominik Beiter; Sokunthea Koy; Steffen Flessa (BMC, 2023)
Abstract Background Cambodia is undergoing a series of reforms with the objective of reaching universal health coverage. Information on the causes of inefficiencies in health facilities could pave the way for a better utilization of limited resources available to ensure the best possible health care for the population. Objectives The purpose of this study is to evaluate the technical efficiency of health centers and the determinants for inefficiencies. Methods This cross-sectional study used secondary data from a costing study on 43 health centers in six Cambodian provinces (2016-2017). Firstly, the Data Envelopment Analysis method with output-orientation was applied to calculate efficiency scores by selecting multiple input and output variables. Secondly, a tobit regression was performed to analyze potential explanatory variables that could influence the inefficiency of health centers. Results Study findings showed that 18 (43%) health centers were operating inefficiently with reference to the variable returns to scale efficiency frontier and had a mean pure technical efficiency score of 0.87. Overall, 22 (51%) revealed deficits in producing outputs at an optimal scale size. Distance to the next referral hospital, size and quality performance of the health centers were significantly correlated with health center inefficiencies. Conclusion Differences in efficiency exist among health centers in Cambodia. Inefficient health centers can improve their technical efficiency by increasing the utilization and quality of health services, even if it involves higher costs. Technical efficiency should be continuously monitored to observe changes in health center performance over time.